2010
DOI: 10.2131/jts.35.257
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of paraquat perturbs immunoglobulin productivity in mouse

Abstract: -Paraquat is one of the most widely used herbicides in the world and has been known to injure lungs, liver and skin in animals and human. Hence, it is important to understand the manner of paraquat in mammals. We studied the effect of paraquat on the immune function of mouse in vitro and in vivo. When splenocytes were cultured in vitro with various concentrations of paraquat, IgA productivity was not affected while IgG and IgM productivity decreased. On the other hand, Oral administration of paraquat for 1, 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Alternatively, IFN-γ and IL-21 mRNA expression was up-regulated at 0.023 μM of PQ, while it was down-regulated at 7.777 μM PQ concentration. Similar observations of PQ varied effects at lower concentrations were documented by Okabe et al 9 These authors observed that PQ resulted in the significant reduction of IgM and IgG but not IgA production in vitro at PQ concentrations between 1 μM and 0.1 nM, but no effect was noted at higher 10 and 100 μM. Considering that the antibody isotype depends on cytokine environment, hence, such findings may corroborate the differential pattern of cytokine gene up-regulation detected at 0.023 versus 7.777 μM.…”
Section: ■ Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Alternatively, IFN-γ and IL-21 mRNA expression was up-regulated at 0.023 μM of PQ, while it was down-regulated at 7.777 μM PQ concentration. Similar observations of PQ varied effects at lower concentrations were documented by Okabe et al 9 These authors observed that PQ resulted in the significant reduction of IgM and IgG but not IgA production in vitro at PQ concentrations between 1 μM and 0.1 nM, but no effect was noted at higher 10 and 100 μM. Considering that the antibody isotype depends on cytokine environment, hence, such findings may corroborate the differential pattern of cytokine gene up-regulation detected at 0.023 versus 7.777 μM.…”
Section: ■ Discussionsupporting
confidence: 88%
“…Moreover, PQ was found to perturb immunoglobulins' isotype production. A recent study showed that daily oral intake of PQ at 0.12–4.2 mg/kg has resulted in decreasing IgM levels while increasing IgA antibodies levels . Despite such evidence of immunotoxicity at subacute doses of PQ, it is not determined yet whether single acute doses at subtoxic concentrations would be immunotoxic.…”
Section: Introductionmentioning
confidence: 99%
“…There are many consequences to human health related to agrochemical exposure. National and international studies have correlated the use of pesticides with chronic adverse effects, such as depression and suicide 27 , respiratory 28,29 , immunological 30,31 , and reproductive disorders [32][33][34] , as well as neurotoxic and teratogenic [35][36][37] , genotoxic 38 , and neurotoxic 39 , and cancer [40][41][42][43] . Although there is limited information about the used types and amount types of pesticides in this studied region, the participants reported using certain high toxic pesticides already banned in most of developed countries such as paraquat and methamidophos.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, PQ was also reported to influence adaptive immune response. For instance, although both increased and decreased levels of serum immunoglobulin (Ig) were reported, most studies suggest that PQ might have a suppressive effect on Ig production [14,15,16,17]. Similarly, numerous studies indicated that PQ increased the number of lymphocytes, while others reported that PQ reduced the number of lymphocytes [14,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Although a variety of studies have been performed to investigate the effects of PQ on immunity [4,14,15,16,17,18,19], to date, the influence of PQ on memory immune response remains incompletely understood. Previously, we performed numerous studies to elucidate the neurotoxicity and lung toxicity of PQ [11,24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%